A case management report: a collaborative perioperative surgical home paradigm and the reduction of total joint arthroplasty readmissions. Issue 1 (December 2016) - Alem, Navid; Rinehart, Joseph; Lee, Brian; Merrill, Doug; Sobhanie, Safa; Ahn, Kyle; Schwarzkopf, Ran; Cannesson, Maxime; Kain, Zeev
Abstract Background Efforts to mitigate costs while improving surgical care quality have received much scrutiny. This includes the challenging issue of readmission subsequent to hospital discharge. Initiatives attempting to preclude readmission after surgery require planned and unified efforts extending throughout the perioperative continuum. Patient optimization prior to discharge, enhanced disease monitoring, and seamless coordination of care between hospitals and community providers is integral to this process. The perioperative surgical home (PSH) has been proposed as a model to improve the delivery of perioperative healthcare via patient-centered risk stratification strategies that emphasize value and evidence-based processes. Results This case report seeks to specifically describe implementation of readmission reduction strategies via a PSH paradigm during total joint arthroplasty (TJA) procedures at the University of California Irvine (UCI) Health. An orthopedic surgeon open to collaborate within a PSH paradigm for TJA procedures was recruited to UCI Health in October of 2012. Institution specific data was then prospectively collected for 2 years post implementation of the novel program. A total of 328 unilateral, elective primary TJA (120 hip, 208 knee) procedures were collectively performed. Demographic analysis reveals the following: mean age of 64 ± 12; BMI of 28.5 ± 6.2; ASA Score distribution of 0.3 % class 1, 23 % class 2, 72 % class 3, and 4.3 % class 4; and 62.5 % female patients. In all, a 30-day unplanned readmission rate of 2.1 % (95 % CI 0.4–3.8) was observed during the study period. As a limitation of this case report, this reported rate does not reflect readmissions that may have occurred at facilities outside UCI Health. Conclusions As healthcare evolves to emphasize value over volume, it is integral to invest efforts in longitudinal patient outcomes including patient disposition subsequent to hospital discharge. As outlined by this case management report, the PSH provides an institution-led means to implement a series of care initiatives that optimize the important metric of readmission following TJA, potentially adding further value to patients, surgical colleagues, and health systems.